Estratégias Acadêmicas para a Promoção da Saúde Mental dos Estudantes de Medicina - Fasanella, Nicoli Abrão (2022)
Introduction: Studies show that one in every five young people has psychological distress. Universities can use various academic strategies to contribute to their student's psychic well-being. Objectives: to develop and describe academic curricular strategies for mental health promotion to protect the mental health of medical students at the Faculty of Medical Sciences and Health at the Pontifical Catholic University of São Paulo (FCMS at PUC-SP). Methods: This is an exploratory research associated with educational activities, which used a detailed analysis of the literature and a previous study at the same institution designed to identify the main reasons for psychological distress among medical students. Different mental health promotion interventions were developed, within the curriculum, with students and teachers in the years 2020 and 2021. Results: Different mental health education materials were prepared, videos and educational reading materials were made available for access in a virtual learning environment platform on key mental health topics. Discussion: The proposed actions were well received and publicized in partnership with the course coordination, PUC-SP FCMS board, faculty as well as with the student entities. They promoted easy access to information on mental health and provoked discussions among all community participants. Conclusions: Mental health care is closely related to education and knowledge regarding health, it also has the potential to stimulate debates on the subject and expand access to knowledge regarding care variants. Studies of such nature can contribute to promoting mental health as well as training doctors with specific skill sets aimed at the well-being of their patients